Start-up acquisitions and innovation strategies - Igor Letina; Armin Schmutzler; Regina Seibel (University of Bern, Department of Economics, 2020)
This paper provides a theory of strategic innovation project choice by incumbents and start-ups. We apply this theory to identify the effects of prohibiting start-up acquisitions. We differentiate between killer acquisitions (when the incumbent does not commercialize the acquired start-up's technology) and acquisitions with commercialization. A restrictive acquisition policy reduces the variety of research approaches pursued by the firms and thereby the probability of discovering innovations. Furthermore, it leads to strategic duplication of the entrant's innovation by the incumbent. These negative innovation effects of restrictive acquisition policy have to be weighed against the pro-competitive effects of preserving potential competition
Keywords: O31; L41; G34; 330; innovation; acquisitions; mergers; competition; start-ups